Rhenium-osmium geochronology and geochemistry of the Upper Jurassic marine black shales, Agardhfjellet Formation, Central Spitsbergen, Svalbard and mercury degradation of Upper Permian shales, East Greenland and mid-Norwegian shelf - Park, Junhee, author; Hannah, Judith, advisor; Harry, Dennis, committee member; Borch, Thomas, committee member; Georgiev, Svetoslav, committee member; Hammer, Øyvind, committee member; Olaussen, Snorre, committee member (Colorado State University. Libraries, 2024)
Every rock has its own story. Rocks are categorized as igneous, metamorphic, and sedimentary types based on their origins and overprinting processes. The human species is confronting the crisis of climate change and some rocks hold a climate story from the past, permitting speculation on the future. On the geological time scale, Earth has experienced both scorching and freezing environments, the latter referred to as Snowball Earth. A critical key to resolving the problems we are facing lies in geology, which deconvolutes environments where specific rocks have formed. This dissertation addresses Boreal sedimentary sections during the Late Jurassic period by conducting three projects; Project I pinpoints depositional ages for black shales from the Agardhfjellet Formation and discusses Os isotopic ratios in the Boreal ocean during the Late Jurassic. Project II evaluates the depositional environments of the Agardhfjellet Formation, which was deposited during a shelf dysoxic-anoxic event. Project III focuses on Hg degradation incurred during incipient weathering and calls attention to interpreting Hg signals of sedimentary rocks, which have been used as an indicator of ancient volcanism. This dissertation provides new radiometric ages and detailed geochemical discussions of the Late Jurassic Agardhfjellet Formation and cautions the use of Hg concentrations when interpreting from outcrop sections. The findings herein significantly enhance our understanding of shelf dysoxic-anoxic events compared with oceanic anoxic events and Hg behavior during the early stage of weathering.
Keywords: black shale; geochronology; Upper Jurassic; geochemistry; Agardhfjellet Formation; Re-Os